2010
DOI: 10.1097/hco.0b013e32833f04b0
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary surgery: where do we stand in 2010?

Abstract: Off-pump coronary artery bypass continues to be a useful technique for coronary revascularization. The benefits of off-pump techniques may be more apparent for patients at high risk for complications associated with cardiopulmonary bypass and aortic manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…With the improvements in methods for coronary artery stabilization and exposure, beating heart surgery, such as OPCAB, has attracted increased interest [ 107 ], but the benefits and risks of an off-pump versus on-pump approach have been debated. Patients in certain patient subgroups, including older patients, females, those with a history of stroke, renal impairment, and pulmonary disease, are considered to benefit more from OPCAB surgery than are other patients [ 134 ]. Numerous studies have confirmed the effectiveness of off-pump surgery compared to on-pump surgery in reducing postoperative renal dysfunction [ 30 , 135–137 ], and renal function might be a factor influencing the choice of revascularization strategy.…”
Section: Preventionmentioning
confidence: 99%
“…With the improvements in methods for coronary artery stabilization and exposure, beating heart surgery, such as OPCAB, has attracted increased interest [ 107 ], but the benefits and risks of an off-pump versus on-pump approach have been debated. Patients in certain patient subgroups, including older patients, females, those with a history of stroke, renal impairment, and pulmonary disease, are considered to benefit more from OPCAB surgery than are other patients [ 134 ]. Numerous studies have confirmed the effectiveness of off-pump surgery compared to on-pump surgery in reducing postoperative renal dysfunction [ 30 , 135–137 ], and renal function might be a factor influencing the choice of revascularization strategy.…”
Section: Preventionmentioning
confidence: 99%
“…For example, manipulating an atherosclerotic ascending aorta during cross-clamping can potentially induce distal embolus formation and cause stroke, especially among elderly high-risk patients. 2 However, the benefit of off-pump in comparison with on-pump coronary artery bypass grafting (CABG) among older and sicker patients is still controversial. 3 Sufficient evidence suggests that off-pump bypass surgery reduces atrial fibrillation, 4 but a Cochrane review including 86 studies (with 10,716 participants) showed no significant benefit from off-pump compared with on-pump CABG in regard to mortality, episodes of stroke, or myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, manipulating an atherosclerotic ascending aorta during cross-clamping can potentially induce distal embolus formation and cause stroke, especially among elderly high-risk patients. 2 However, the benefit of off-pump in comparison with on-pump coronary artery bypass grafting (CABG) among older and sicker patients is still controversial. 3…”
Section: Introductionmentioning
confidence: 99%
“…A lthough off-pump coronary artery bypass (OP-CAB) grafting is an accepted approach for multivessel coronary revascularization that offers low mortality rate and postoperative morbidity, [1][2][3][4] several previous observational studies have reported suggestive evidence that OPCAB may also be associated with increased rates of repeat vascularization and major vascular events after hospital discharge. 5,6) Furthermore, numerous surgeons consider OPCAB more technically challenging and less cost-effective than the on-pump approach due to more resources being consumed. 7) Therefore, minimally invasive direct coronary artery bypass (MIDCAB) has been suggested as an alternative strategy to address these issues and is currently gaining wide acceptance among clinicians.…”
mentioning
confidence: 99%